Brucella suis biovar 1 infection in a dog with orchitis in Germany - Aurich, Sophie; Schneider, Juliane; Brangsch, Hanka; Koets, Ad; Melzer, Falk; Ewers, Christa; Prenger-Berninghoff, Ellen (Frontiers in Veterinary Science, 2023)
In 2021, a case of canine brucellosis was diagnosed in a dog with ascending orchitis presented to a veterinary practice in Germany. Serologic testing excluded Brucella (B.) canis as causative agent, but molecular analysis revealed the presence of B. suis biovar 1. Since biovar 1 is not endemic in Europe and the dog had no history of travel to endemic areas, a comprehensive epidemiological investigation was conducted using whole genome sequence data to determine the source of infection. We describe the clinical progress in the animal and a potential infection of a veterinary clinic employee. The findings highlight the importance of considering less common Brucella species as a possible cause of canine brucellosis. The data also emphasize that it is quite challenging to identify Brucella species in a routine diagnostic laboratory and to conduct epidemiological investigations to unveil possible transmission routes.